Vertical and spanwise wake flow structures of a single spire over smooth wall surface in a wind tunnel - Fitriady, Muhammad Arifuddin; Nurizzatul Atikha, Rahmat; Ahmad Faiz, Mohammad (Isfahan University of Technology, 2023)
The aerodynamic interaction between the wake flow structure behind a single spire with a smooth wall boundary layer at a long streamwise location was observed in a wind tunnel experiment. The application of a single spire is intended to generate a wake flow similar to the one generated behind a skyscraper. A quarter elliptic wedge spire was used and a long streamwise distance of up to 26 times the spire’s height was adopted to ensure the development of the boundary layer and the wake recovery. To grasp how the smooth wall boundary layer interacts with the wake as well as how the wake recovers downstream, vertical and lateral velocity profiles were examined. Despite only one spire being utilized, it was found that the role of the spire as a vortex generator was confirmed the boundary layer height in the with-spire case increased compared to that of the without-spire case. Moreover, the velocity deficit recovery process was observed vertically and streamwise. However, within the boundary layer, the recovery rate in the streamwise direction was lower compared to the above it. This finding indicates that within the boundary, the turbulence generated can sustain the wake caused by the spire, reducing the recovery rate. Based on the current lateral velocity analysis, the final streamwise distance required by the wake to fully recover could not be predicted due to the large velocity deviation of 2.15% at the end of the streamwise distance.